A Complete Postversion of the Three-Body Continuum Distorted Wave-Eikonal Initial State Approximation for Single Ionization of Multielectron Atoms. (12th April 2010) - Monti, J. M.; Fojón, O. A.; Hanssen, J.; Rivarola, R. D.
Abstract : Single electron ionization of helium targets produced by the impact of fast proton beams is investigated. The postversion of the continuum distorted wave-eikonal initial state into a three-body approximation is reformulated, including the dynamic screening produced by the nonionized electron. This dynamic screening is shown to play a main role in the determination of double differential cross-sections. A good agreement is found with predictions obtained employing the prior version of the model, so that post-prior discrepancies are almost eliminated.